Effect of surface wetting resin on the color stability and microhardness of esthetic composites = Efecto de la resina humectante de superficies sobre la estabilidad del color y la microdureza de resinas compuestas estéticas - Cangul, Suzan
Objective: The aim of this study was to evaluate and compare the effects of the superficial application of two different modeling resins on the surface microhardness and discoloration of composite resins. Material and Methods: The present study used two different composites and modeling resins. The composites were placed in plastic molds. Subsequently, the modeling resins were applied on the surface of the two composite groups. The microhardness and color pertaining to all the groups were evaluated. The current study used the One-Way ANOVA and Kruskal Wallis tests, in order to perform the statistical evaluation (p<0.05). Results: The present study compared the microhardness pertaining to the groups and the highest microhardness values were observed in the Estelite Asteria group (none), whereas the lowest values were observed in the GC Essentia group (Ultradent). Moreover, the current study evaluated the color stability and the greatest discoloration was observed in the control group of the GC Essentia group, whereas the least discoloration was observed in the Estelite Asteria group that included the samples prepared using Ultradent Wetting Resin. Conclusions: The results of the present study demonstrated that the use of modeling resins, which facilitate the placement of composite resins, reduced the microhardness and discoloration of composite resins. The aforementioned effect can be attributed to the variations in the structure of the filling. However, further studies are warranted to support and verify the results of the current study.